The Influence of Social Media Against Interest in Buying Kopilogi Products - Salma Fitri Nurfauziah; Nizar Alam Hamdani (Entrepreneurship Faculty, Universitas Garut, 2021)
This study discusses the influence of social media on interest in buying copilogy products. The relationship used in this study is a causal relationship with 60 Garut domiciled consumer respondents who have already tried their products. The data analysis technique used is simple regression with the application of SPSS 20. The measurement scale used by researchers is the interval scale. This study uses primary data and secondary data obtained from books, journals, literature, scientific works from the internet with relevant sources. The primary data collection technique in this study is an online questionnaire that contains a number of structured statements given to respondents through Google forms and respondents provide answers based on a Likert scale of 1-5, starting from 1 (strongly disagree) to 5 (strongly agree). The conclusion of this research is the significant effect between the influence of Social Media on Kopilogi Buy Interest.